THE IMPACT OF LIQUIDITY RISK OPTIMIZATION ON STABILITY - Maria Lusiana Yulianti; Rosmiati Pakata; Nanok Fitriyadi. S (Jurnal Ekonomi, 2023)
This research was conducted with the aim of knowing the effect of liquidity risk on bank stability with credit risk and operational efficiency as intervening variables for Islamic Commercial Banks in Indonesia for the 2012-2021 period. This study uses secondary data on the financial reports of Islamic commercial banks issued by the financial services authority (OJK) for the period 2012 to 2021. The sample was taken using a non-probability sampling technique, namely purposive sampling in order to obtain 10 Islamic commercial banks. The analysis technique is carried out by testing 6 (six) hypotheses. The results of this study indicate that liquidity risk can have a direct effect on bank stability, but there are also credit risk and operational efficiency variables play a role in mediating the relationship to the stability of the bank. Meanwhile, liquidity risk is not able to directly affect the operational efficiency of the bank.